KETERPURUKAN SEKTOR PERTANIAN SEBAGAI POTRET KEGAGALAN INDUSTRIALISASI DI INDONESIA - Grendi Hendrastomo * (Dimensia: Jurnal Kajian Sosiologi, 2011)
Shifting agricultural era to the era of industrialization left many problems, especially in the agricultural sector. Populist policies have on one hand brought the country many industrial investments that force economic growth, but on the other hand reduced the partisanship of country in agricultural sector. Agriculture as the basis for mass production of most Indonesian society has became casualties as part of the green revolution that is full of developing countries‘s propaganda which brings benefit and lead to dependency on developing countries. The downturn actors of agricultural field increased in line with growth of food-estate program to attract foreign investors to explore the agro sector. This article discusses on a critical review of agriculture in Indonesia’s slump that began with the green revolution with their panca usaha tani, starting from the decline of the agricultural sector, static industrial situation until the solutions that might be applied to enhance the economic growth and social dynamics of Indonesia.   Keywords: Industrialisation, Marginalization of Agriculture, Green Revolution